Leader Member Exchange and Employee Voice Behaviour : The Mediating Role of Employee Engagement - Erni Nurrafika; Chichi Andriani (Human Resource Management Studies, 2022)
This study aims to determine the effect of leader member exchange on employee voice behavior with employee engagement as a mediator. The population in this study were employees of PT Supraco Mitra Energie, Hiliran Gumanti District, Solok Regency. The sample used is 50 employees. Data collection is done through distributing questionnaires and data processing is done through smart PLS3. The results of this study indicate that the leader member exchange has a positive and significant effect on employee voice behavior, leader member exchange has a positive and significant effect on employee engagement, employee engagement has a positive and significant effect on employee voice behavior and the exchange of leaders and members has a positive and significant effect on behavior. employee voice with employee engagement as a mediating variable.